Histopathological Study of Mucormycosis in Post COVID-19 Patients and Factors Affecting it in a Tertiary Care Hospital. (February 2023) - Sree Lakshmi, I.; Kumari, B. Swapna; Jyothi, Ch.; Devojee, M.; Padma Malini, K.; Sunethri, Padma; Bheemrao Somalwar, Shrinivas; Kavitha, T.
Introduction. COVID-19 is an infection caused by severe acute respiratory syndrome corona virus-2 (SARS-CoV-2) which may be associated with a wide range of bacterial and fungal co-infections. Mucormycosis is an opportunistic fungal infection occurring in post COVID-19 patients. Objectives. To study the role of histopathology in mucormycosis and the predisposing factors associated in development of mucormycosis in post COVID-19 patients. Materials and methods. A prospective observational study was conducted in our hospital in the pathology department over a period of 3 months on 200 patients with mucormycosis who were infected with SARS-CoV-2 virus. Results. Out of the 200 patients with mucormycosis studied in post COVID-19 patients, age ranged from 21–80 years, of which 132 were men and 68 were women. Sites involved by mucormycosis were sinuses, orbit, cranium, and cutaneous. Ethmoid sinus was most involved, followed by maxillary sinus. Diabetes was present in 162 patients and hypertension in 92 patients. On histopathological examination, fungal load was severe in 49 patients, angioinvasion was present in 48 patients, perineural invasion was present in 32 patients, and necrosis was present in 121 patients. The number of patients discharged after surgery was 169, whereas 31 died. Conclusion. Histopathological features of mucormycosis like angioinvasion, perineural invasion, severe fungal load, and large areas of necrosis were directly proportional to the mortality rate. Thus, histopathologists can help in assessing prognosis at the time of tissue diagnosis, so that clinicians can optimize treatment accordingly. Diabetes and history of corticosteroid intake for treatment of COVID-19 were the two commonest predisposing factors for development of mucormycosis.